Effects of 12‐week resistance training during radiotherapy in breast cancer patients. (5th October 2016) - Wiskemann, J.; Schmidt, M. E.; Klassen, O.; Debus, J.; Ulrich, C. M.; Potthoff, K.; Steindorf, K.
Abstract : Exercise is considered to be an effective supportive treatment approach in breast cancer (BC) patients. We conducted a randomized controlled trial to assess the efficacy of a 12‐week PRT during radiotherapy. Strength performance was assessed by maximal isokinetic peak torque (MIPT) in two different angular velocities (60°/s and 180°/s) and maximal voluntary isometric contraction for shoulder external and internal rotation, as well as for knee extension and flexion were assessed pre‐ and post‐intervention in 146 patients randomized to PRT or a control group. Statistical analyses were based on analysis of covariance models for the individual changes from baseline to week 13. Intention‐to‐treat analyses showed significant between‐group differences favoring the exercise group (EX) for MIPT in knee flexion and shoulder internal and external rotation ( P < 0.05). Subgroup analyses showed borderline significant differences with regard to pretreatment history, revealing that pretreated chemotherapy patients tend to benefit more from PRT than patients without chemotherapy ( P = 0.06). Strength gain at the operated arm was significantly higher than at the non‐operated arm in EX. PRT was efficacious in increasing upper and lower limb strength in BC patients undergoing adjuvant radiotherapy. Patients with restrictions due to breast cancer‐related surgery and pretreated with chemotherapy might benefit the most.